Those who were better off: Capital and top incomes in Fascist Italy - Giacomo Gabbuti (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
In the centennial of the March on Rome, this paper contributes to the political economy of Italian Fascism by addressing in quantitative terms the fortunes of Italian economic elites during the interwar period. Macro-economic indicators indicate capital accumulation and high profits, in a period characterised by international economic turmoil, alongside increasing concentration. New fiscal evidence is adopted to show the increasing relative position of the rich, including new series of top income shares. A discussion of taxation at the top and its evasion makes it possible to place these developments within the regressive economic policies of the Fascist regime.
Keywords: D31; D63; E25; J31; N34; 330; Fascist Italy; income inequality; interwar Europe; top incomes; capital